The pathway of the fawn : a tale of the New Year - Hervey, T. K., Mrs., 1811-1903 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1852)
Bertha is forced by her father to masquerade as a boy in order to bar the succession of his nephew, Heinrich, to the family estates. She is secretly learning sculpting from her cousin who lives in the vicinity with his sister, Roschen, and his mother. Two local landowners and friends discover love in unexpected places: Ernst sees through Bertha's disguise and declares his love; and Moritz meets Roschen and vows to marry her. After many trials, revelations, an illness and a strayed letter the two pairs of lovers find happiness.